Chambers, Robert. Can we know better? Reflections for development. Rugby, Reino Unido, Practical Action Publishing, 2017 - Betancor Álvarez, Marta (Revista Española de Desarrollo y Cooperación, 2020)
Reseña de la obra de Chambers, Robert. Can we know better? Reflections for development. Rugby, Reino Unido, Practical Action Publishing, 2017.